The different predictive value of mean platelet volume-to-lymphocyte ratio for postoperative recurrence between non-muscular invasive bladder cancer patients treated with intravesical chemotherapy and intravesical chemohyperthermia - Wang, Chengbo; Jin, Wenjun; Ma, Xiaodong; Dong, Zhilong (Frontiers in Oncology, 2023)
Introduction The inflammatory response plays a potential role in postoperative recurrence in patients with non-muscular invasive bladder cancer (NMIBC). We aimed to investigate whether platelet-to-lymphocyte ratio (PLR), mean platelet volume to lymphocyte ratio (MPVLR), and the systemic immune-inflammatory index (SII) have prognostic values in NMIBC treated with conventional intravesical chemotherapy or intravesical Chemohyperthermia (CHT) and the differences between them. Materials and methods A retrospective cohort study was conducted on 222 patients with NMIBC treated with Intravesical Chemotherapy or Intravesical CHT between January 2016 and December 2020. Within a week before surgery, PLR, MPVLR, and SII were determined based on routine blood settling. The optimal cutoff value of each index was determined using the receiver operating characteristic curve, and various groups were categorized accordingly. The factors influencing the prognosis of NMIBC patients receiving various treatments were investigated using the Kaplan- Meier survival curve and the Cox regression model. Results 69 cases (46.3%) in the gemcitabine (GEM) group had tumor recurrence and 19 (12.8%) of them progressed to muscle-invasive bladder cancer (MIBC) or got metastasis, while 19 cases (26.0%) in the CHT group recurred and 2 (2.7%) progressed. Elevated PLR, MPVLR, and SII were associated with higher recurrence rates in the GEM group. Meanwhile, PLR and MPVLR were the independent risk factors. While in the CHT group, high PLR and SII were related to postoperative recurrence and none of them were independent risk factors. Conclusion The preoperative clinical inflammatory indexes PLR, SII, and MPVLR have certain predictive value for the postoperative recurrence-free survival (RFS) in NMIBC patients treated with intravesical chemotherapy while PLR and SII can predict the prognosis of NMIBC patients treated with intravesical CHT, which indicates that intravesical CHT may stop tumor recurrence by influencing the effect of mean platelet volume on tumor growth through some unknown mechanisms.